REITs ante portas: die Anpassung des deutschen Rechts an institutionelle Investoren in den Grundstücks- und Mietmärkten - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2008)
In the US or in the UK, the presence of institutional investors in real estate markets is an old phenomenon. Specifically, Real Estate Investment Trusts are an old industry. Due to a difference in tax law, the market share of REITs in Germany has been minimal until very recently. Now the legislator has extended the tax privileges held by real estate funds to REITs, expecting that the change will make Germany an attractive place for international investors in these markets. While the effect on capital markets is planned, the German legislator has not been very attentive to likely side effects on the proper functioning of real estate law, landlord and tenant law, and zoning law. The paper analyses these effects, and points to potential legislative concerns.
Keywords: K11; 340; Immobilienfonds; Institutioneller Anleger; Wohnungswirtschaft; Grundstücksrecht; Mietrecht; Baurecht; Deutschland